WAKTU BELAJAR VS PENGUASAAN BAHASA YANG DIHARAPKAN SISWA DI SEKOLAH INDONESIA - Erik Pebrikarlepi (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2022)
Effective time management plays a crucial role in the learning process. This study analyzes the interaction between learning time and the English language mastery expected from students in Indonesia. This research uses a qualitative approach with descriptive research to collect data through observation, interview, and documentation. Based on the Academic Learning Time (ALT) theory, academic learning time includes time allocation, level of student engagement, and level of student success. Time allocation in the curriculum is considered an important factor in achieving learning objectives, but the lack of English learning time is an issue. Teachers often spend time with inefficient practices such as copying questions on the board. In addition, large class sizes and limited time allocation limit the effectiveness of learning. Proposed solutions include extended learning time, more efficient teaching strategies, and integration of out-of-class learning. Furthermore, practical guidelines from other researchers, such as the use of class time for authentic interactions, student motivation, and out-of-class learning links, can help improve students' time management and English language acquisition. Collective efforts from schools, teachers and stakeholders can help overcome these challenges and improve English learning outcomes in Indonesia.